Edukasi Kegawatdaruratan Hipertensi Dalam Meningkatkan Pengetahuan Lansia Dengan Hipertensi - Arif Hidayatullah; Eka Rokhmiati (Jurnal Masyarakat Mengabdi Nusantara, 2023)
Hypertension is a condition in which blood vessels have high blood pressure (systolic blood pressure ≥140 mmHg or diastolic blood pressure ≥ 90 mmHg). Hypertension is often referred to as the silent killer because it can attack anyone suddenly and it is a disease that can result in death. This community service aims to invite the public to understand the emergency management of the elderly with hypertension. This community service was carried out for 30 people with hypertension at RT 013 RW 007 Kel. Kedaung Kec. Cengkareng, West Jakarta. This activity was carried out on July 8 2022, including; checking blood pressure and education on emergency management of elderly people with hypertension. The knowledge evaluation instrument uses a hypertension knowledge questionnaire and blood pressure assessment using a sphygmomanometer. Providing emergency education for the elderly with hypertension increases the knowledge score, the score before is 42 and the score after is 83 so that the post-test score increases 98% from the pre-test score. The results of blood pressure examinations for elderly people with BP > 140/90 mmHg were 21 people (70%) and elderly people with BP < 140/90 mmHg were 9 people (30%). Providing emergency education for the elderly with hypertension can increase the knowledge of the elderly regarding hypertension so that their quality of life is maintained.